Leadership of Madrasah Principals in Fostering Professional Work Ethic among Educational Staff: A Case Study in Indonesian Islamic Schools - Mawardi; Elza Eka Putri; Mona Novita; Darma Wisata (Al-Qalam Institue, 2025)
This study aims to examine how madrasah principals enact leadership practices to foster professional work ethic among educational staff in Indonesian Islamic schools. Educational institutions are not only sites of knowledge transmission but also arenas for cultivating ethical conduct and professional discipline. In madrasah contexts, professional work ethic is inseparable from the moral legitimacy of institutions grounded in Islamic values. Employing a qualitative case study design, data were collected through semi-structured interviews, participant observation, and document analysis. Thematic analysis was used to interpret leadership practices within their organizational and cultural contexts. The findings show that values-based leadership, enacted through moral exemplarity and ethical modeling, is a primary driver of the formation of a professional work ethic. Participatory and relational leadership strengthens organizational commitment, trust, and work discipline by fostering psychological ownership and inclusive governance. Ethical norms are institutionalized through formal routines and informal socialization, enabling the reproduction of professional standards beyond direct supervision. Leadership influence operates at micro, meso, and macro levels through exemplarity, participation, and cultural embedding. These mechanisms jointly cultivate self-regulation, accountability, and service orientation. This study contributes an integrative, culturally grounded framework for ethical leadership in faith-based education and recommends leadership development programs that emphasize ethical embodiment, participatory governance, and institutionalized routines.